The accommodation coefficient of water molecules on ice – cirrus cloud studies at the AIDA simulation chamber - J. Skrotzki (Atmospheric Chemistry and Physics, 2013)
Cirrus clouds and their impact on the Earth's radiative budget are subjects of current research. The processes governing the growth of cirrus ice particles are central to the radiative properties of cirrus clouds. At temperatures relevant to cirrus clouds, the growth of ice crystals smaller than a few microns in size is strongly influenced by the accommodation coefficient of water molecules on ice, αice, making this parameter relevant for cirrus cloud modeling. However, the experimentally determined magnitude of αice for cirrus temperatures is afflicted with uncertainties of almost three orders of magnitude, and values for αice derived from cirrus cloud data lack significance so far. This has motivated dedicated experiments at the cloud chamber AIDA (Aerosol Interactions and Dynamics in the Atmosphere) to determine αice in the cirrus-relevant temperature interval between 190 K and 235 K under realistic cirrus ice particle growth conditions. The experimental data sets have been evaluated independently with two model approaches: the first relying on the newly developed model SIGMA (Simple Ice Growth Model for determining Alpha), the second one on an established model, ACPIM (Aerosol-Cloud-Precipitation Interaction Model). Within both approaches a careful uncertainty analysis of the obtained αice values has been carried out for each AIDA experiment. The results show no significant dependence of αice on temperature between 190 K and 235 K. In addition, we find no evidence for a dependence of αice on ice particle size or on water vapor supersaturation for ice particles smaller than 20 μm and supersaturations of up to 70%. The temperature-averaged and combined result from both models is αice = 0.7−0.5+0.3, which implies that αice may only exert a minor impact on cirrus clouds and their characteristics when compared to the assumption of αice =1. Impact on prior calculations of cirrus cloud properties, e.g., in climate models, with αice typically chosen in the range 0.2–1 is thus expected to be negligible. In any case, we provide a well-constrained αice which future cirrus model studies can rely on.